COUNSELING AND ASSISTANCE FOR HOTEL AND RESTAURANT TAX IN BANYUMAS REGENCY: PENYULUHAN DAN PENDAMPINGAN PAJAK HOTEL DAN RESTORAN DI KABUPATEN BANYUMAS - Aan Kanivia; Icuk Rangga Bawono (Yayasan Education and Social Center, 2021)
Taxes are a source of income for local governments, where the government uses tax revenues to build facilities and infrastructure for the community's public interest. Given the importance of the role of the community in bearing state financing, it is demanded that public awareness, both private and corporate, be required to pay taxes. The hotel, entertainment and restaurant sector is one of the largest sources of tax absorption. Where is the restaurant sector most major wherein the 2020 pandemic became a sector whose realization exceeded the target in Banyumas Regency. The hotel tax is one of the two tax sectors that did not reach the target in 2020. The method used in the implementation of this community service activity was lectures and discussions. This activity results in the people in Banyumas Regency, especially hotel and restaurant owners, getting a lot of input and information about the importance of taxes, calculating hotel and restaurant taxes, and paying hotel and restaurant taxes. In addition, it is hoped that this activity can increase the awareness of hotel and restaurant owners regarding the importance of taxes and the obligation to pay hotel and restaurant taxes by the provisions of the legislation